Reflections on artistic creation - Silva Rojas, Terencia Inés (2020)
This work aims to reflect on a topic that can be as broad as we want, covering various fields of knowledge and that concerns all artistic disciplines. Our objectives are more modest. Our intention is not to arrive at a definition of creation, but simply to approach this complex process. To fulfill this purpose, we prepared a questionnaire that was distributed to a small number of artists (twelve in total) from different fields of art: music, plastic arts, literature, etc.